On interface closeness and problem solving - Donahue, Thomas J.; Poor, G. Michael; Mott, Martez; Leventhal, Laura Marie; Zimmerman, Guy; Klopfer, Dale (ACM Conference on Tangible, Embedded and Embodied Interaction (TEI), 2013)
Prior research suggests that "closer" interface styles, such as touch and tangible, would yield poorer performance on problem solving tasks as a result of their more natural interaction style. However, virtually no empirical investigations have been conducted to test this assumption. In this paper we describe an empirical study, comparing three interfaces, varying in closeness (mouse, touchscreen, and tangible) on a novel abstract problem solving task. We found that the tangible interface was significantly slower than both the mouse and touch interfaces. However, the touch and tangible interfaces were significantly more efficient than the mouse interface in problem solving across a number of measures. Overall, we found that the touch interface condition offered the best combination of speed and efficiency; in general, the closer interfaces offer significant benefit over the traditional mouse interface on abstract problem solving.